A defined community of core gut microbiota members promotes cognitive performance in honey bees - Amélie Cabirol; Andrew Quinn; Julie Schafer; Nicolas Neuschwander; Lucie Kesner; Joanito Liberti; Philipp Engel (Proceedings of the National Academy of Sciences, 2026)
Gut microbiota across animals have been shown to influence host cognition and behavior. However, it remains unclear whether these cognitive effects are driven by specific bacterial species or arise from community-level interactions. Here, we leveraged the honey bee ( Apis mellifera ) as a model system, which harbors a simple and well-characterized gut microbiota that is experimentally tractable and has been previously shown to impact host cognition. We established a defined bacterial community—composed of core members of the honey bee gut microbiota. Gnotobiotic bee experiments with the full community, communities missing individual members, or individual members showed that only the full community enhanced honey bees’ performances in odor discrimination learning and short-term memory compared to microbiota-deprived bees. Metabolomic analyses identified several metabolites associated with learning success that mapped to pathways modulated by microbial colonization, including tryptophan metabolism, nucleoside metabolism, and lysine degradation. However, many of these metabolites were not altered by removing individual members from the full microbial community. This suggests that microbiota-mediated improvements in cognition are emergent properties of the community as a whole, rather than the result of individual metabolites or specific bacterial taxa acting alone. Our findings support a systems-level view of the microbiome, suggesting that understanding and manipulating host development, particularly in relation to brain function, should prioritize microbial community function (e.g., metabolic pathways) over taxonomic composition alone.